Analisis Faktor Ibu yang Pernah Bersalin Nomal Mengalami Risiko Bedah CCaesarea - siti maisyaroh fitri siregar (Jurnal Maternitas Kebidanan, 2019)
ABSTRACT The objective of the research was to analyze the risk factors of women with the history of normal childbirth had delivery by section caesarea. The research used observational analytic method with case-control study design. The samples consisted of 42 cases and 42 controls, taken by using consecutive sampling technique. Dependent variable was childbirth with CS and independent variables were parity, accompanied illness, and reference. The gathered data were analyzed by using univatriate analysis, bivariate analysis with chi square test, and multivatriate analysis at α = 0.05. The result of the research from multivariate analysis showed that the variables which had significant influence on childbirth with SC were parity (p = 0.006; OR = 5.801 95% CI = 1.642-19.110),accompanied illness (p = 0.03; OR = 6.382 95% CI = 1.198-33.992), and reference (p = 0.003; OR = 6.350 95% CI = 1.874-21.522). The variable which had the most dominant influence childbirth with CS was accompanied illness. p-value = 97% which indicated that childbirth women with the parity > 2 had accompanied illness and the reference to the hospital had the possibility to give birth with CS of 97%. It is recommended to do family planning programme, and prevent the illness during pregnant, apply ANC according to the standard, and make sure that the childbirth is safe from Period I to Period III. Keywords: Risk Factor, Caesarea, Case-Control